RELASI SOSIAL-EKONOMI SEKAA CAK RAMAYANA DI KOMPLEK PURA ULUWATU, BADUNG, BALI - Sanjay Wikrama, I Wayan Etong; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The existence of the Cak Ramayana dance performed by SekaaCakKarangBomo in the Uluwatu Temple complex is very well maintained. Unlike the conditions of some SekaaCak in other regions in which the performance is not every day or the audience is not as crowded as the performance in Uluwatu. The thing that causes this condition to happen is the existence of a social network that is micro, meso and macro. This social network will bring about socio-economic relations.The actors involved in the performance establishedthe socio-economic relations with several parties. Personally, SekaaCakmembersbuilttherelations with the guide. The relations also occurred between the members of SekaaCak and Dese Pekraman, and SekaaCak with travel agent. Applying embeddednes theory from Granovetter as an analysis tool, this relationscouldbe established because of an embeddednes. The embeddednes involved in this performance could be classified into weak-strong embeddednes, relational embeddednes and structural embeddednes. Keywords: Social network, Social economic relations, Sekaa Cak, embededdness.